A contribuição da avaliação de desempenho, como um instrumento de apoio à decisão, para a prevenção ao crime baseada no ambiente - Tasca, Jorge Eduardo (2013)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia de Produção, Florianópolis, 2013.Abstract : Since the incorporation of the principles of Administrative Theory, in the early twentieth century, through areas of knowledge as diverse as medicine, psychology, geography, statistics, urbanism, architecture, and others, researchers and managers crime prevention has been worth the knowledge produced in many different fields of science to improve and innovate their methods and forms of intervention. It is in this context, that the theme of this research is to propose the incorporation in place-based (physical and human) crime prevention, with repercussions also on victims and offenders, the assumptions of another area of knowledge, performance evaluation as an instrument for decision aid. To prove the scientific contribution of this bias performance evaluation in place-based crime prevention, this thesis employed as technical procedures bibliographic research and case study, and used on the methodological tools ProKnow-C (Knowledge Process Development - Constructivist) and MCDA - C (Multicriteria Decision Aid - Constructivist). With ProKnow-C, was selected a relevant and aligned bibliographic references to the research topic, stressing the periodicals, articles, authors and keywords highlighted, and held a systemic analysis of the literature, identifying knowledge gaps and opportunities for scientific contribution in six analysis lenses - Approach; Singularity; Identification of objectives; Measurement; Integration, and Management. Already MCDA - C, was applied to a case study on the scope of the 1st Company of the 4th Military Police Battalion, in Florianópolis-SC, to test and demonstrate the potential scientific contributions of this study. The results obtained at the end of the research confirmed the scientific contributions of the six assumptions of performance evaluation as a instrument for decision aid in place-based crime prevention, especially the adoption of the constructivist approach and management process